The Effect of Capital Structure, Financial Risk and Investment Opportunities on Company Financial Performance in the Port Sector with the Principles of Corporate Governance (GCG) as Variable Intervening (Financial Management Literature Review) - Adhyatma, Adhyatma (Dinasti Publisher, 2023)
Literature review article on the influence of capital structure, financial risk and investment opportunities on company financial performance in the port sector with the principles of corporate governance (GCG) as intervening variables is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research , within the scope of Financial Management science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) Capital Structure influences Company Financial Performance in the Port Sector with the Principles of Corporate Governance (GCG) as an Intervening Variable; 2) Financial Risk affects the Company's Financial Performance in the Port Sector with the Principles of Corporate Governance (GCG) as an Intervening Variable; and 3) Investment Opportunities affect the Company's Financial Performance in the Port Sector with the Principles of Corporate Governance (GCG) as an Intervening Variable. Apart from these 3 exogenous variables that influence the endogenous variables of Company Financial Performance in the Port Sector with the Principles of Corporate Governance (GCG) as Intervening Variables there are still many other factors including the variables x4, x5 and x6.